Core decompression with bone chips allograft in combination with fibrin platelet-rich plasma and concentrated autologous mesenchymal stromal cells, isolated from bone marrow: results for the treatment of avascular necrosis of the femoral head after 2 years minimum follow-up. Issue 2 (December 2020) - Rocchi, Martina; Del Piccolo, Nicoladrea; Mazzotta, Alessandro; Giavaresi, Gianluca; Fini, Milena; Facchini, Fabio; Stagni, Cesare; Dallari, Dante
Introduction: Avascular necrosis of femoral head (AVN) is 1 of the main factors causing disability in young adults. Hip prosthesis can be considered an effective treatment of the painful symptoms but it is a major surgical intervention for this type of population. Thus, a large space should be left to therapeutic alternatives such as regenerative medicine. This retrospective study evaluates 52 AVN treated by core decompression, bone chips allograft, fibrin platelet-rich plasma (PRF) and concentrated autologous mesenchymal stromal cells (MSCs). Methods: The AVN was diagnosed using magnetic resonance imaging (MRI) and graded according to ARCO classification: a patient was classified stage 1 (21 patients), stage 3 (26 patients), and 4 patients were classified as stage 4. We evaluated patients with functional scores (Harris Hip Score) and radiological analysis at 3, 6, 12 and 24 months after the procedure. Patients requiring prosthetic replacement of the joint were included; in these cases, follow-up was interrupted at the time of the joint replacement procedure. Results: Our statistical analysis showed differences between survived and failed treatments, in terms of patient profile and ARCO radiological classification. The best result occurred in patients with ARCO grades 1 and 2, while the more advanced grades showed a high failure rate. It is interesting to note that ARCO quantification, conceived as the joint surface involved in the necrosis, has a negative influence on the outcome of the procedure. Indeed, patients affected by ARCO 3a, where necrosis involved a small portion of the femoral epiphysis and the collapse of the articular surface was limited to 2 mm, showed results similar to those obtained in patients with ARCO 1 and 2. Conclusions: In conclusion, compared with the alternative technique of decompression, our data suggest that post-collapse cases with a small area of necrosis and the use of bone grafts may show better results compared to those of the literature.